2018
DOI: 10.1007/s00705-018-3869-8
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary analyses of Sindbis virus strains isolated from mosquitoes in Kenya

Abstract: Sindbis virus (SINV) is a mosquito borne virus maintained in nature in a mosquito-bird cycle, with human outbreaks known to occur in Northern Europe and parts of Africa. We analyzed five SINV strains isolated in Kenya from five different mosquito species and geographic locations between 2007 and 2013. Phylogenetic relationships and evolutionary inferences were performed using maximum likelihood and Bayesian phylogenetic inference approaches. Selection analyses were carried out based on the virus envelope glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…pipiens in the MMNR is likely due to vertical or environmental transmission. SINV has been isolated from Culex and Aedes mosquito species in Kenya (Sigei et al, 2018) and has been found in a Cx. pipiens mosquito that had fed on human blood in Baringo County, Kenya (Omondi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…pipiens in the MMNR is likely due to vertical or environmental transmission. SINV has been isolated from Culex and Aedes mosquito species in Kenya (Sigei et al, 2018) and has been found in a Cx. pipiens mosquito that had fed on human blood in Baringo County, Kenya (Omondi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Kenya harbors more than 80 different Aedes species () but not all have been associated with the spread of mosquito viruses. An important species is A. ochraceus which is highly distributed in the arid regions of north-eastern Kenya and linked to the spread of Rift Valley fever virus (RVFV), NDUV, Bunyamwera virus (BUNV), Babanki virus (BBKV), Sindbis virus (SNBV), and Semliki Forest virus (SMFV) in the region [4,11,34,35,36,37,38]. Additionally, this species has also been reported to be associated with RVFV, dengue virus (DENV), and chikungunya virus (CHKV) in coastal counties (Kwale, Kilifi, Mombasa, Lamu) [11,33,39], and some parts of in the western region [22].…”
Section: Overview Of the Main Mosquito Genera Of Public Health Impmentioning
confidence: 99%
“…Virus circulation outside of Europe has been detected primarily based upon virus isolation and serology in native populations rather than outbreaks of Sindbis disease. SINV has been isolated from mosquitoes in Kenya [302]. South Africa has reported infections but underreporting is highly likely as Sindbis disease may be attributed to other illnesses with similar symptoms [259].…”
Section: Potential For Future Outbreaksmentioning
confidence: 99%